AB0873 Us rheumatologists have mixed perceptions about managing patients with non-radiographic axial spondyloarthritis and ankylosing spondylitis. (12th June 2018) - Robinson, J.; Price, L.
Abstract : Background: Non-radiographic axial spondyloarthropathy (nrAxSpA) is a relatively new term used to describe patients who clinically appear to have ankylosing spondylitis (AS) but do not exhibit radiographic sacroilitis. Though several biologics are currently FDA approved for the treatment of AS, there are no agents approved for patients in which there is not radiographic evidence of sacroilitis. With several agents under investigation with the hopes of gaining a line-extension label for nr-axSpA, it is important to understand how the current treating rheumatologists view these two diseases and their current and future plans for spondyloarthropathy management. Objectives: The study sought to (a) evaluate the differences between AS and nr-axSpA diagnosis and treatment patterns (b) highlight the challenges clinicians face in managing patients with nr-AxSpa and (c) understand rheumatologists' willingness to use biologic agents to treat nr-AxSpa. Methods: An independent market analytics firm collaborated with US rheumatologists (n=98) to learn about current and anticipated changes to the management of Ankylosing Spondylitis and Non-radiographic Axial Spondylitis. Participants were administered an online survey, lasting approximately 30 min in length and respondents were compensated for their professional time. Following the fieldwork, data were analysed in SPSS, a statistical software, to determine significant differences. Results: 87% of the surveyed rheumatologists agree that AS and nr-AxSpA are part of a spectrum, and 37% report that they often find it challenging to differentiate between the two conditions. The majority of the respondents report that they treat these conditions in a very similar manner. In fact, 40% agree that distinguishing between the two has no relevance to their treatment decisions. Use of biologics is significantly more pronounced in AS (56% vs. 39%, respectively), largely because there is currently no FDA indicated biologic for nr-AxSpA and because many rheumatologists view nr-AxSpA simply as a less severe precursor to AS, where aggressive treatment with a biologic is not warranted. In order to gain reimbursement for a biologic in patients with nr-AxSpA, rheumatologists frequently classify patients as having AS (as opposed to nr-AxSpA). Although adalimumab is the most frequently prescribed biologic in both conditions, rapid adoption of an IL-17 inhibitor (secukinumab) is occurring in the US market. Conclusions: There is a need to educate both primary care physicians and rheumatologists about the differences between AS and nr-AxSpA. The official FDA approval of biologic agents in nr-AxSpA is anticipated to lead to more aggressive treatment of these patients earlier in the spectrum. Reference: [1] RealTime Dynamix TM : Anlylosing Spondylitis and Non-radiographic Axial Spondylitis Disclosure of Interest: None declared